2009
DOI: 10.1103/physrevb.80.125420
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes of Pd-Au bimetallic nanoclusters upon hydrogenation

Abstract: Changes in the size distribution and composition of bimetallic Pd-Au nanoclusters have been observed after hydrogen exposure. This effect is caused by hydrogen-induced Ostwald ripening whereby the hydrogen reduces the binding energy of the cluster atoms leading to their detachment from the cluster. The composition changes due to a difference in mobility of the detached palladium and gold atoms on the surface. Fast palladium atoms contribute to the formation of larger nanoclusters, while the slower gold atoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…106,107 Pd 0.7 Au 0.30 single crystal surface after vacuum annealing is strongly enriched by gold. 106 Di Vece et al 108 observed changes in the size distribution and composition of bimetallic PdAu nanoparticles that have been exposed to hydrogen at RT. The effect was identified to be due to Ostwald ripening of Pd after Pd has segregated to the surface.…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%
“…106,107 Pd 0.7 Au 0.30 single crystal surface after vacuum annealing is strongly enriched by gold. 106 Di Vece et al 108 observed changes in the size distribution and composition of bimetallic PdAu nanoparticles that have been exposed to hydrogen at RT. The effect was identified to be due to Ostwald ripening of Pd after Pd has segregated to the surface.…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%
“…This chemical sensitivity through the Z dependence allows compositional effects to be studied, such as core-shell effects (e.g. Garcia-Gutierrez et al 2004) or quantitative elemental analysis (Di Vece et al 2009;Epicier et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…16 While there is no general consensus on this topic, a wide range of values of α (1.3-2) has been used in the literature, [17][18][19][20][21][22][23][24][25][26][27] often without a full evaluation of microscope conditions. This situation hinders wider applications of quantitative STEM in nanomaterials characterization.…”
mentioning
confidence: 99%